Reduction in intensity of Pneumocystis carinii pneumonia in mice by aerosol administration of gamma interferon. - Beck, J M (1991)
Pneumocystis carinii pneumonia in patients with AIDS may result from impaired local release of gamma interferon from lung lymphocytes and subsequent failure of macrophage activation. We tested this hypothesis with mice rendered immunodeficient by selective depletion of CD4+ lymphocytes and inoculated intratracheally with P. carinii. After aerosol administration of recombinant murine gamma interferon, the intensity of P. carinii infection in these mice was reduced in comparison with that in mice not treated with gamma interferon. Histologic scoring of lung tissue did not reveal additional pulmonary inflammation attributable to gamma interferon. Aerosol administration of gamma interferon may reduce the intensity of P. carinii infection by augmentation of host defense, despite persistent CD4+ lymphocyte depletion.